Nilai-nilai kearifan lokal dan peranannya dalam pengelolaan pembangkit listrik tenaga mikrohidro (PLTMh) di Kasepuhan Ciptagelar: Local wisdom values in the management of microhydro power plants (PLTMh) in Kasepuhan Ciptagelar - Dimas Aji Saputra Saputra; Berliana Intan Maharani; Gita Dewi Aprillia; Masiroh Masiroh; Ilham Pahlawi; Sartini Sartini (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
: This research examines the local wisdom values of the Kasepuhan Ciptagelar indigenous community which play a role in managing micro-hydro power plants as a source of renewable energy. The method used in this research is qualitative with a phenomenological approach. Three key informants in this research were selected through the purposive sampling technique. Data collection was obtained through field observations, in-depth interviews, and literature studies. The results show that the management of the micro-hydro power plant in Kasepuhan Ciptagelar involves several local wisdom values which are manifested in the form of local knowledge, beliefs, views of life, customs and daily activities that rely on the values and norms. The local wisdom values that are important in managing micro-hydro power plants include the concept of “Leuweung tutupan” or forbidden forest and the tradition of “Melak tangkal di tahun anyar” by planting trees every new year. The result of this research shows that the local wisdom of the Kasepuhan Ciptagelar community is the most important social capital in managing micro-hydro power plants to fulfill electrical energy needs independently in everyday life.